Return to work after aneurysmal subarachnoid hemorrhage - Sorteberg, Angelika; Lashkarivand, Aslan; Western, Elin (Frontiers in Neurology, 2024)
Survivors of aneurysmal subarachnoid hemorrhage (aSAH) often recover without severe physical or cognitive deficits. However, strikingly low levels of engagement in productive employment have been reported even in aSAH patients with good or excellent outcome. Knowledge about return to work (RTW) after aSAH and predictors for no RTW remain limited and controversial. The aim of the study was to delineate the return to maximum work capacity up to five years after the ictus in a larger number of consecutive aSAH patients from the entire aSAH severity specter, and to identify demographic and medical predictors of no RTW. Data were acquired from a prospective institutional database. We included all 500 aSAH survivors aged > 18 years that were treated between January 2012 through March 2018. Alongside work status and type of work at ictus we retrieved demographical data, and aSAH severity by quantification of subarachnoid, intraventricular, and intraparenchymal blood as well as the World Federation of Neurological Societies (WFNS) grade. We registered the mode of aneurysm repair (endovascular or surgical) and complications like vasospasm, new acquired cerebral infarctions and chronic hydrocephalus. Work status and grade of fatigue at follow-up were registered. RTW was assessed in the 299 patients that were employed at ictus, 63.2% were female and their age was 51.3±9.4 (20-71 years). Return to gainful employment was 51.2%, with complete RTW accounting for 32.4%. Independent predictors of no RTW were age at ictus, WFNS grade 3, and active smoking. The strongest independent predictor was the presence of clinically significant fatigue which 5-folded the risk to not returning to work. The chance to return to gainful employment significantly increased with years of education an individual had prior to their hemorrhage. Mode of aneurysm repair was not relevant with regard to RTW. Patients in WFNS grades 1-2 more often returned to work than those in WFNS grades 3-5, but our results can indicate that neurological motor deficits are linked closer to no RTW than aSAH severity per se. Fatigue needs to be addressed as an important element on the path to return to work integration.